(untitled) (Terr@ Plural, 2011)
The characteristics of the riparian zones are important for the entrance of materials into the stream, such as sediment and woody debris. This is caused by the close connection between hillside, stream and land use along the river banks. These relationships directly affect the dynamics of the river. Example of land use that affects stream dynamics is the livestock grazing on riparian zones on “faxinal” systems, which significantly changes the characteristics of vegetation and accelerates the organic debris entrance in waterways. This study examined the influence of woody debris in some parameters of the river dynamics on “faxinal” areas, such as: flow velocity, flow, channel geometry, volume of debris in the channel, the stream depth, particle size and morphology of the sediments in the streambed, while also performing the characterization of the vegetation present in the riparian zone. It was found that the woody debris had a direct effect on the evaluated parameters.